Combination Dabrafenib and Trametinib Versus Combination Nivolumab and Ipilimumab for Patients With Advanced BRAF-Mutant Melanoma: The DREAMseq Trial—ECOG-ACRIN EA6134. Issue 2 (27th September 2022) - Atkins, Michael B.; Lee, Sandra J.; Chmielowski, Bartosz; Tarhini, Ahmad A.; Cohen, Gary I.; Truong, Thach-Giao; Moon, Helen H.; Davar, Diwakar; O'Rourke, Mark; Stephenson, Joseph J.; Curti, Brendan D.; Urba, Walter J.; et al.
Abstract : PURPOSE: Combination programmed cell death protein 1/cytotoxic T-cell lymphocyte-4–blockade and dual BRAF/MEK inhibition have each shown significant clinical benefit in patients with BRAFV600 -mutant metastatic melanoma, leading to broad regulatory approval. Little prospective data exist to guide the choice of either initial therapy or treatment sequence in this population. This study was conducted to determine which initial treatment or treatment sequence produced the best efficacy. PATIENTS AND METHODS: In a phase III trial, patients with treatment-naive BRAFV600 -mutant metastatic melanoma were randomly assigned to receive either combination nivolumab/ipilimumab (arm A) or dabrafenib/trametinib (arm B) in step 1, and at disease progression were enrolled in step 2 to receive the alternate therapy, dabrafenib/trametinib (arm C) or nivolumab/ipilimumab (arm D). The primary end point was 2-year overall survival (OS). Secondary end points were 3-year OS, objective response rate, response duration, progression-free survival, crossover feasibility, and safety. RESULTS: A total of 265 patients were enrolled, with 73 going onto step 2 (27 in arm C and 46 in arm D). The study was stopped early by the independent Data Safety Monitoring Committee because of a clinically significant end point being achieved. The 2-year OS for those starting on arm A was 71.8% (95% CI, 62.5 to 79.1) and arm B 51.5% (95% CI, 41.7 to 60.4; log-rank P = .010). Step 1 progression-free survival favored arm A ( P = .054). Objective response rates were arm A: 46.0%; arm B: 43.0%; arm C: 47.8%; and arm D: 29.6%. Median duration of response was not reached for arm A and 12.7 months for arm B ( P < .001). Crossover occurred in 52% of patients with documented disease progression. Grade ≥ 3 toxicities occurred with similar frequency between arms, and regimen toxicity profiles were as anticipated. CONCLUSION: Combination nivolumab/ipilimumab followed by BRAF and MEK inhibitor therapy, if necessary, should be the preferred treatment sequence for a large majority of patients.